2012
DOI: 10.1016/j.dcn.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of selective attention on academic foundations: A cognitive neuroscience perspective

Abstract: To the extent that selective attention skills are relevant for academic foundations and amenable to training, they represent an important focus for the field of education. Here, drawing on research on the neurobiology of attention, we review hypothesized links between selective attention and processing across three domains important to early academic skills. First, we provide a brief review of the neural bases of selective attention, emphasizing the effects of selective attention on neural processing, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(213 citation statements)
references
References 170 publications
(187 reference statements)
4
197
0
12
Order By: Relevance
“…In this regard, different studies seem to confirm that the benefits of cognitive training transfer to real life situations (see Klinghbergh et al, 2005;Rueda, Rothbart, McCandliss, Saccomano, & Posner, 2005;Stevens & Bavelier, 2012;Stevens, Fanning, Coch, Sanders, & Neville, 2008). It seems that the amazing plasticity of the brain facilitates the correction of maladaptive information processing habits enabling the individual to perform effectively in real-world contexts.…”
Section: Interventions and Brain Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, different studies seem to confirm that the benefits of cognitive training transfer to real life situations (see Klinghbergh et al, 2005;Rueda, Rothbart, McCandliss, Saccomano, & Posner, 2005;Stevens & Bavelier, 2012;Stevens, Fanning, Coch, Sanders, & Neville, 2008). It seems that the amazing plasticity of the brain facilitates the correction of maladaptive information processing habits enabling the individual to perform effectively in real-world contexts.…”
Section: Interventions and Brain Plasticitymentioning
confidence: 99%
“…With this in mind, this paper intends to provide a different perspective by indicating that certain characteristics like personal traits and the influence of a caring adult like a teacher, provides the pillars to reverse the harmful effects of poverty. Besides, the implementation of intervention and cognitive training programs are potentially beneficial, correcting cognitive features such as maladaptive information processing styles that impede school achievement (D'Angiulli, Herdman et al, 2008;D'Angiulli, Weinbergh et al, 2008;Lutz et al, 2009;Neville et al, 2013;Stevens & Bavelier, 2012). Consequently, we believe that teachers are in a particularly optimal position to help students with attentional problems.…”
Section: Introductionmentioning
confidence: 99%
“…Decision-making is associated with confidence, and confidence guides decisions [63,64]. The more you are unconfident, the less planning you use [30][31][32][33][34]40].…”
Section: Discussionmentioning
confidence: 99%
“…The more you are unconfident, the less planning you use [30][31][32][33][34]40]. Selfconfidence is inherently linked to self-identity [5,64]. A study in a sample of adolescents and adults (aged between 11 and 41 years) indicated that confident judgments ability improves across the period of adolescence, is highest in late adolescence and stabilizes in adulthood [14].…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à direção, a atenção pode ser interna, quando o indivíduo se volta para os processos mentais introspectivos e reflexivos, ou externa, quando está voltada para o mundo externo da pessoa (Garcia-Ogueta, 2001). A seletividade atencional se refere à priorização dos estímulos em detrimento de outros, na focalização de uma determinada parte do ambiente de forma sustentada enquanto, simultaneamente, ignora-se estímulos irrelevantes (Stevens & Bavelier, 2012). Quanto à vigilância, a atenção pode ser vigil, quando ocorre a fixação da atenção sobre determinado estímulo, ou difusa, que corresponde à incapacidade da pessoa para se concentrar em uma determinada área e faz com que ocorra a focalização de estímulos que estão dispersos (Desimone & Duncan, 1995;Sternberg, 2000).…”
Section: A Atençãounclassified